The Impact of COVID-19 on 'Spanish-Speaking' Children's Phonological Development - Marían Acero-Ferrero; Raquel Lozano-Blasco; María Jesus Cardoso Moreno; Sandra Benaque Giner (MDPI AG, 2024)
Communication and social interaction have been limited during the COVID-19 pandemic. The aim of this study was to check if 3-, 4-, and 5-year-old children manifest alterations in oral language according to their stage of language development. To carry it out, the Induced Phonological Register developed by Monfort and Juárez was applied to analyze 150 participants (77 boys and 73 girls) with an average age of 4 years and 6 months. Children who experienced the COVID-19 pandemic for an extended period show a delay in the acquisition of some phonemes compared to children who undergo typical phonological development as specified by Laura Bosch (2003) regarding language development for Spanish children. Likewise, they present a higher number of erroneous words and phonemes than expected for their age.